A supply-demand model for communication of transit signal priority requests. (6th January 2009) - Tan, Chin-Woo; Li, Meng; Park, Sungsu; Liu, Hongchao; Lau, Peter; Xu, Qing
A critical issue encountered in implementing a transit signal priority system is to ensure that communication between transit vehicles and the traffic centre can be established for transmitting signal priority requests and vehicle arrival time information needed for executing signal priority control at signal-controlled intersections. The available communication channel bandwidth, however, is not guaranteed to meet the demand from a potentially large number of transit vehicles requesting signal priority service. In this paper, we define and analyse this supply-demand problem with simulations of a simple time model. The emphasis is to investigate the logistic issues and identify the critical parameters, so that this simple model might serve as a framework for constructing a more complex realistic model upon which an efficient scheduling protocol could be designed to meet signal priority service demand.